1968
DOI: 10.2514/3.4767
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear vibrations of an infinitely long cylindrical shell.

Abstract: the transformed equation X"' + a.X" + b-X' + d-X + c = 0 (4) By making a further transformation of the type X + c /d = Y (5) we obtain 7'"+ aF" + 67'-+ d-7 = 0 (6) Equation (6) is a third-order linear differential equation and hence represents the equivalent linear system in the transformed plane (Y-T). Equation (6) can easily be solved to obtain F as a function of T. Using Eqs. (3) and (5) along with the solution to Eq. (6) gives, say, From Eq. (2),Substitution of Eq. (7) in (8) gives the relation between t a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…However, the criticism raised by Evensen (1977) Some studies have addressed fluid-structure interaction in a light medium, like air, considering shell nonlinearity. For example, the nonlinear flutter of a circular cylindrical shell in supersonic flow was studied by Olson & Fung (1967) and Evensen & Olson (1967, 1968. In particular, Olson & Fung (1967) discussed the calculation of the aerodynamic pressure with the aid of both linear piston theory and potential flow theory; numerical results were obtained by using piston theory and a mode expansion involving two asymmetric modes having a different axial wavenumber plus two axisymmetric terms.…”
Section: Nonlinear Vibrations Of Shells With Fluidmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the criticism raised by Evensen (1977) Some studies have addressed fluid-structure interaction in a light medium, like air, considering shell nonlinearity. For example, the nonlinear flutter of a circular cylindrical shell in supersonic flow was studied by Olson & Fung (1967) and Evensen & Olson (1967, 1968. In particular, Olson & Fung (1967) discussed the calculation of the aerodynamic pressure with the aid of both linear piston theory and potential flow theory; numerical results were obtained by using piston theory and a mode expansion involving two asymmetric modes having a different axial wavenumber plus two axisymmetric terms.…”
Section: Nonlinear Vibrations Of Shells With Fluidmentioning
confidence: 99%
“…He studied the free vibrations and the response to a modal excitation without considering damping and discussed the stability of the response curves. Evensen (1968) extended his work to infinitely long shells vibrating in a mode in which the generators of the cylindrical surface remain straight and parallel, by using the method of harmonic balance, without considering the companion mode. He also wrote an interesting review paper (Evensen 1974).…”
Section: Circular Cylindrical Shells In Vacuomentioning
confidence: 99%
See 2 more Smart Citations
“…Readers interested by these works can turn to [1] and [2] or to the review paper presented recently by [3], and to a more recent review paper by [4], in which a set of papers are discussed and commented. It can be observed that although several works exist in literature on nonlinear vibrations of shells, only few papers are available which are concerned with the nonlinear free vibration of shells of infinite length.…”
Section: Introductionmentioning
confidence: 99%